The screening and anti-Raji lymphoma effect of Chiloscyllium plagiosum anti-CD20 VNARs - Ren, Qingyu; Sheng, Yu; Sun, Ling; Zheng, Feijian; Hu, Chengwu; Chen, Jianqing; Lyu, Zhengbing; Yuan, Chen; Jiang, Xiaofeng (Frontiers in Marine Science, 2024)
IntroductionB-cell lymphoma, a malignant proliferative disease originating from lymphoid tissue, poses a grave threat to human health. CD20 has emerged as a promising target for lymphoma treatment. However, due to the significant heterogeneity of B-cell lymphomas, conventional CD20 monoclonal antibodies show limited penetration, severely impeding the progress of B-cell lymphoma therapies.MethodsIn contrast, single-domain antibody molecules derived from cartilaginous fish have a molecular weight as small as 12 kDa, granting them robust penetration capabilities and making them the smallest known molecules of efficiently targeting specific antigens.ResultsAs a result, these molecules hold tremendous potential as candidate drugs for lymphoma treatment. In this study, the whitespotted bamboo shark (Chiloscyllium plagiosum) was immunized with recombinant human CD20 to generate specific single-domain antibodies (sdAbs) targeting CD20. By utilizing phage display technology, the variable new antigen receptors (VNARs) were successfully screened and identified, and play an important role in the inhibition of Raji lymphoblastoma.DiscussionThe sdAbs obtained through this research represent promising candidates for B-cell lymphoma treatment, displaying significant potential for clinical applications and offering a new direction for the development of targeted therapies against lymphoma.